INTERLANGUAGE RESTRUCTURING IN LEGO-MEDIATED GRAMMAR LEARNING AMONG YOUNG EFL LEARNERS: Restrukturisasi Interlanguage dalam Pembelajaran Simple Present Tense Berbasis Lego pada Pembelajar EFL Usia Muda - Ni Luh Desy Suari Dewi; I Gede Neil Prajamukti Wardhana; Ni Nyoman Tri Sukarsih (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Grammar acquisition remains one of the most challenging aspects of English as a Foreign Language (EFL) learning, particularly for young learners who often experience difficulties in understanding English morphosyntactic systems such as the Simple Present Tense. This study investigates how young EFL learners demonstrate interlanguage restructuring during Lego-mediated grammar learning through visual-symbolic learning activities. A descriptive qualitative design with classroom action research procedures was employed in this study. Data were collected through classroom observation, learners’ sentence construction tasks, interviews, and questionnaires. The analysis focused on identifying interlanguage features such as auxiliary misuse, subject–verb disagreement, verb inflection errors, and sentence transformation difficulties.The findings revealed that learners initially produced various interlanguage forms, including incorrect auxiliary usage and incomplete subject–verb agreement. However, after participating in Lego-mediated learning activities, learners gradually demonstrated more target-like grammatical constructions. The use of color-coded Lego structures appeared to increase learners’ grammatical awareness by making morphosyntactic relationships more visually salient. The findings further suggest that visual-symbolic mediation facilitated learners’ noticing of grammatical patterns and supported interlanguage restructuring during Simple Present Tense acquisition. Therefore, Lego-mediated grammar learning may provide valuable support for young EFL learners in developing English morphosyntactic competence.